Atmospheric pressure plasma deposition of eugenol-derived film on metallic biomaterial for suppression of Escherichia coli and Staphylococcus aureus bacterial biofilm - Getnet, Tsegaye Gashaw [UNESP]; Kayama, Milton E. [UNESP]; Rangel, Elidiane C. [UNESP]; Duarte, Iolanda C.S.; da Silva, Gabriela F; Cruz, Nilson C. [UNESP] (Elsevier, 2021)
Eugenol (4-Allyl-2‑methoxy phenol) is widely used as a condiment and bactericidal coatings for food packing and biomaterials. We have investigated the deposition and characterization of eugenol-derived films (EDF) on stainless steel surfaces deposited using atmospheric pressure plasma discharge for suppression of Escherichia coli and Staphylococcus aureus bacterial adhesion and proliferation. The thickness of the deposited films was in the range of 1,000 to 2,500 nm with a roughness up to 800 nm. Infrared spectra showed that the EDF preserves the hydroxyl and aromatic groups found in liquid eugenol, which is a key feature for the antibacterial activity of the film. X-ray photoelectron spectroscopy analysis has revealed increased oxygen content with the deposition time. Scanning electron microscopy has shown that the entire surface of the substrate is covered by a circular structure approximately 10 to 20 µm in diameter. Wettability analysis revealed an increase in the hydrophilicity of the surface after the deposition. Microbiological evaluation of bacterial growth, revealed that the surfaces inhibited the adhesion and proliferation of E. coli and S. aureus by more than 78 and 65%, respectively, while in the untreated samples the growth was greater than 90% for both microbes in comparison with polystyrene plates used as a positive control. Therefore the eugenol thin film deposited by this method was effective for biofilm suppression with a potential application for biocompatible material coating processes.
Keywords: Biofilm inhibition; Dielectric barrier discharge; Eugenol; Plasma polymer